Molecular Mechanisms of Potato Plant–Virus–Vector Interactions - Roza Kenzhebekova; Alexandr Pozharskiy; Kamila Adilbayeva; Dilyara Gritsenko (Plants)
Viral infections and their vector dynamics pose a major threat to potatoes (Solanum tuberosum L.) worldwide, urgently needing an integrated understanding of the molecular and ecological interactions in this tripartite system. This review describes the major potato viruses, namely potato virus Y (PVY), the potato leafroll virus (PLRV), and potato virus X (PVX), with an emphasis on their infection and replication strategies in plants, as well as their movement within them. It also discusses plant responses to these viruses by uncovering RNA silencing, resistance (R) genes, and hormonal signaling. The complex dynamics of virus–vector interactions are discussed, considering the modes of transmission-persistent, non-persistent and semi-persistent—the role of viral proteins such as HC-Pro in determining vector specificity and adaptations in vectors that facilitate virus dissemination. This article discusses how vectors select potato plants, with an emphasis on the role played by plant-excreted volatiles and vector-applied saliva in plant defense. It also discusses host genes that contribute to vector resistance. This review provides an overview of the interactions between potato plants, viruses, and vectors and shows how viruses influence plant–vector interactions, the molecular pathways shared, and the altered gene expression profiles due to these interactions. The review offers an integrated perspective essential for developing sustainable and precise control strategies against potato viral pathogens under changing climatic conditions.